2007
DOI: 10.1016/j.visres.2006.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Luminance texture increases perceived speed

Abstract: Previous psychophysical experiments have demonstrated that various factors can exert a considerable influence on the apparent velocity of visual stimuli. Here, we investigated the effects of superimposing static luminance texture on the apparent speed of a drifting grating. In Experiment 1, we demonstrate that superimposing static luminance texture on a drifting luminance modulated grating can produce an increase in perceived speed. This supports the hypothesis that texture changes perceived speed by providing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 62 publications
2
3
0
Order By: Relevance
“…We suppose that the increase of the perceived speed in the enriched road environments resulted from the addition of relative motion cues as vehicle motion was then viewed against the reference points. This interpretation would be in line with previous studies showing a similar increase of perceived speed with the addition of a static visual surrounding (e.g., Blakemore and Snowden, 2000, Brown, 1931, Gogel & McNulty, 1983, Nguyen-Tri & Faubert, 2007. In terms of the interpretation of the speed bias observed in fog, the fact that perceived speed increased in both simple and more enriched road environments suggests that a bias in the perceived vehicle distance may not be the primary driver.…”
Section: Discussionsupporting
confidence: 90%
“…We suppose that the increase of the perceived speed in the enriched road environments resulted from the addition of relative motion cues as vehicle motion was then viewed against the reference points. This interpretation would be in line with previous studies showing a similar increase of perceived speed with the addition of a static visual surrounding (e.g., Blakemore and Snowden, 2000, Brown, 1931, Gogel & McNulty, 1983, Nguyen-Tri & Faubert, 2007. In terms of the interpretation of the speed bias observed in fog, the fact that perceived speed increased in both simple and more enriched road environments suggests that a bias in the perceived vehicle distance may not be the primary driver.…”
Section: Discussionsupporting
confidence: 90%
“…In general, the perceived speed of a central region is greatly increased when its surround moves in the opposite direction (Norman, Norman, Todd, & Lindsey, 1996) but is reduced by a surround moving in the same direction (Loomis & Nakayama, 1973;Walker & Powell, 1974). To some extent, this is dependent on the relative velocity of the surround (Loomis & Nakayama, 1973;Norman et al, 1996), but similar effects have been reported recently with static surrounds (Blakemore & Snowden, 2000;Nguyen-Tri & Faubert, 2007). Related effects of facilitation and inhibition also occur when the stimuli are arranged in adjacent rows (Bressan, 1991;Nawrot & Sekuler, 1990).…”
Section: Introductionsupporting
confidence: 65%
“…We have shown that a simple model of motion sensing that implements a subtractive interaction between motion sensors tuned to high and low spatial frequencies can account for the facilitation effect; however, there are other results that could explain our facilitation effect. For example, it has been found that static luminance texture increases perceived speed (Nguyen-Tri & Faubert, 2007). These authors found that when a static grating of 2 c/deg was added to a moving grating of 0.5 c/deg, the perceived speed of the low-frequency pattern increased 1.25 times.…”
Section: Discussionmentioning
confidence: 99%